Effect of vermiwash of Eisenia foetida produced by different methods on seed germination of green mung, Vigna radia - Amita Chattopadhyay (International Journal of Recycling of Organic Waste in Agriculture)
Vermiwash contains enzymes, macro and micronutrients that could stimulate the growth and yield of crops. It can be prepared by different ways. In the present study, vermiwash was produced from the earthworm, Eisenia foetida, under field condition and also in the laboratory under cold and heat stress methods. These washes were used in different ratios for seed germination of mung, Vigna radiate. The results showed that the vermiwash produced by cold stress diluted at the ratio of 1:5 showed 100 % germination of mung seed followed by 1:5 ratio vermiwash produced naturally that resulted 95 % of seed germination. Undiluted vermiwash produced naturally and by cold stress showed 90 % of germination of mung seed than the undiluted vermiwash produced by heat stress. Cold stress produced vermiwash diluted with 1:5 ratio showed a vigour index of 1650 followed by naturally produced 1:5 ratio diluted vermiwash which showed a vigour index of 1092. However, the undiluted naturally produced vermiwash showed the lowest vigour index of 450.